2015
DOI: 10.1177/0954407015595908
|View full text |Cite
|
Sign up to set email alerts
|

On joint mobility design in multi-structural systems

Abstract: This article aims to develop a measure that can estimate the isolator performance in joint design problems. The relationships between the receptances of the connection points and the isolator bushes in multi-structural car-body systems are explored from the perspective of a frequency-response-function-based substructuring method. From the formulation for the frequency-response-function-based substructuring method, the desirable magnitude difference between the receptances is proposed through an order analysis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…It should be noted that the fractional derivative model parameters, log(a 1 ) and log(c 1 ), are linearly correlated, because the ratio of the parameters log(a 1 /c 1 ) physically represents the asymptotic value of the storage modulus in a high frequency region. 10 The EDR method 24 was used to generate a response PDF at a given h and a gradient-based optimizer, the ''fmincon'' function of MATLAB, 25 was used to solve the unconstrained optimization problem in equation (8). Table 1 lists the identified uncertainties in terms of the fractional derivative model parameters.…”
Section: Characterization Of Uncertaintiesmentioning
confidence: 99%
See 2 more Smart Citations
“…It should be noted that the fractional derivative model parameters, log(a 1 ) and log(c 1 ), are linearly correlated, because the ratio of the parameters log(a 1 /c 1 ) physically represents the asymptotic value of the storage modulus in a high frequency region. 10 The EDR method 24 was used to generate a response PDF at a given h and a gradient-based optimizer, the ''fmincon'' function of MATLAB, 25 was used to solve the unconstrained optimization problem in equation (8). Table 1 lists the identified uncertainties in terms of the fractional derivative model parameters.…”
Section: Characterization Of Uncertaintiesmentioning
confidence: 99%
“…In general, the amounts of response variation differ between vehicles, even for the same elastomer, because the sensitivity of the joint in which the elastomer is attached changes according to the relative relationships of the structures. 8 Figure 15 presents the estimated variabilities of the reaction forces at the joints and the transmitted powers through the joints due to the uncertainties of the elastomers. The variabilities of the reaction forces and the transmitted powers, as depicted in Figure 15, are significantly less than the variability of the vibrational response.…”
Section: A Passenger Car Problemmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to reduce the simulation time but to maintain highly accurate results, as explained by Klerk et al, 10 the DS is based on the principle of dividing a large structure into smaller subsystems which are easier and faster to study. 11 The DS approach is not a new way of working, since the idea was probably introduced by Hurty, 12,13 which led to a constant increase in the interest in DS, resulting in the classic methods of Craig and Bampton, [14][15][16][17] MacNeal 18 and Rubin. 19 The Craig-Bampton method uses two sets of vibrational modes to reduce the system.…”
Section: Introductionmentioning
confidence: 99%
“…These studies have revealed the important role of the chiral 3NF yielding many promising results, see [15] and references therein. For a progress report on the discretized formulation of nuclear chiral EFT see [16]. Still, the well-known discrepancies between state-of-the-art theoretical calculations and experimental data in the three-nucleon continuum at intermediate energies of E N ∼ 50 .…”
Section: Introductionmentioning
confidence: 99%